2013
DOI: 10.1016/j.biortech.2013.01.063
|View full text |Cite
|
Sign up to set email alerts
|

5-Hydroxymethylfurfural induces ADH7 and ARI1 expression in tolerant industrial Saccharomyces cerevisiae strain P6H9 during bioethanol production

Abstract: The aims of this work were to obtain, by evolutionary engineering, an industrial strain of Saccharomyces cerevisiae tolerant to high concentrations of HMF and to determine the expression levels of genes previously described as responsible for this tolerance. Cells were grown under anaerobic and oxygen limited conditions, in the presence of glucose or sucrose as carbon sources. P6H9 strain presented high expression levels for genes ADH7 and ARI1 in presence of HMF. This tolerant strain also showed higher ethano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 33 publications
1
25
0
Order By: Relevance
“…Overexpression of the dehydrogenase/reductase genes ADH6 , ADH7 , ARI1 and ALD6 increased enzyme activities for furfural and/or HMF reduction and concomitantly improved the tolerability of the host S. cerevisiae strains towards the inhibitors (Petersson et al ., ; Liu et al ., ; Liu and Moon, ; Park et al ., ). Consistent with those results, the expression levels of some dehydrogenase/reductase genes, such as ADH6 , ADH7 and ARI1 , showed much higher expression levels in the evolved inhibitor‐tolerant S. cerevisiae strains (Heer et al ., ; Liu et al ., ; Sehnem et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…Overexpression of the dehydrogenase/reductase genes ADH6 , ADH7 , ARI1 and ALD6 increased enzyme activities for furfural and/or HMF reduction and concomitantly improved the tolerability of the host S. cerevisiae strains towards the inhibitors (Petersson et al ., ; Liu et al ., ; Liu and Moon, ; Park et al ., ). Consistent with those results, the expression levels of some dehydrogenase/reductase genes, such as ADH6 , ADH7 and ARI1 , showed much higher expression levels in the evolved inhibitor‐tolerant S. cerevisiae strains (Heer et al ., ; Liu et al ., ; Sehnem et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…In S. cerevisiae , it has been shown that adaptation was at least partially due to an induction of alcohol dehydrogenases. A furfural concentration of 2 g/L induced an ADH activity increase by 78% in 48 H ; in another study, increased ADH transcription in response to exposure to 5‐hydroxymethylfurfural has been described . Therefore, we investigated transcription of ADH genes in adapted and nonadapted cells.…”
Section: Discussionmentioning
confidence: 94%
“…Adaptation of S. cerevisiae to lignocellulose by cultivation in medium containing furfural in batch , fed‐batch , and continuous culture has previously been reported. In a recent study, we showed adaptation of D. bruxellensis to lignocellulose .…”
Section: Discussionmentioning
confidence: 98%
“…Effect of Chlortetracycline on Ammonia Removal.T h e limiting factor of alkalinity on nitrification was excluded by maintaining an alkalinity and nitrogen ratio of 9.46 in all nitrification experiments (Jin et al, 2015;Sehnem et al, 2013). In contrast to the COD removal rate, the effect of chlortetracycline on alkalinity was not significant (p .…”
Section: Resultsmentioning
confidence: 99%